Changes in six domains of cognitive function with reproductive and chronological ageing and sex hormones: a longitudinal study in 2411 UK mid-life women - Fanny Kilpi; Ana Luiza G. Soares; Abigail Fraser; Scott M. Nelson; Naveed Sattar; Sean James Fallon; Kate Tilling; Deborah A. Lawlor (BMC, 2020)
Abstract Background There may be changes in cognitive function in women going through the menopause. The current evidence remains unclear, however, whether these changes occur over and above those of general ageing. We aimed to evaluate the potential impact of the menopause (assessed by reproductive age and hormone levels) on cognitive function in women in mid-life accounting for the underlying effects of ageing. Methods The study was based on the follow up of women originally enrolled in pregnancy in a birth cohort when resident in the South West of England, UK between 1991 and 1992. Using up to three repeated measurements in 2411 women (mean age 51 at first assessment), we modelled changes in six cognitive function domains: immediate and delayed verbal episodic memory, working memory, processing speed, verbal intelligence and verbal fluency. The exposures of interest were reproductive age measured as years relative to the final menstrual period (FMP), chronological age and reproductive hormones (follicle-stimulating hormone (FSH), luteinizing hormone (LH) and anti-Müllerian hormone (AMH)). Results Processing speed (− 0.21 (95% CI − 0.36 to − 0.06) standard deviation (SD) difference per 10 years since FMP), immediate verbal episodic memory (− 0.15 (95% CI − 0.35 to 0.06)) and delayed verbal episodic memory (− 0.17 (95% CI − 0.37 to 0.03)) declined with reproductive age. Reproductive hormones were not robustly associated with processing speed, but FSH and LH were both negatively associated with immediate (− 0.08 (95% CI − 0.13 to − 0.02) SD difference per SD difference in hormone level) and delayed verbal episodic memory (− 0.08 (95% CI − 0.13 to − 0.03)). There was little consistent evidence of cognitive function declining with menopause in other cognitive domains. Conclusions Of the cognitive domains tested only verbal episodic memory declined both in relation to age since the menopause and in conjunction with the reproductive hormones that reflect the menopause. This decline was independent of normal ageing and suggests that the menopause is associated with a mild impact on this specific domain of cognitive function.